2013
DOI: 10.1590/s0103-05822013000300018
|View full text |Cite
|
Sign up to set email alerts
|

Effects of maternal nicotine on breastfeeding infants

Abstract: OBJECTIVE To assess scientific evidence about the effects of maternal nicotine on infant by an integrative review. DATA SOURCES Studies published in Portuguese, English and Spanish, from 1990 to 2009, with abstracts available in the Latin American Health Sciences Literature (Lilacs) and Medical Literature Analysis and Retrieval System On-Line (Medline) databases. The descriptors were: "breastfeeding", "lactation" and "smoking". DATA SYNTHESIS The main identified effects of nicotine on infants were: changes in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0
17

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(51 citation statements)
references
References 19 publications
2
32
0
17
Order By: Relevance
“…According to the results, mothers who smoked had less time to breastfeed their infant. The negative impact of maternal smoking on infant growth and sleep and other infant conditions has been proven before (25,26), however, this study indicated that smoker mothers generally cared less about their children's health and development. Breastfeeding trainings provided by health centers should give them the motivation to quit smoking, too.…”
Section: Discussionmentioning
confidence: 54%
“…According to the results, mothers who smoked had less time to breastfeed their infant. The negative impact of maternal smoking on infant growth and sleep and other infant conditions has been proven before (25,26), however, this study indicated that smoker mothers generally cared less about their children's health and development. Breastfeeding trainings provided by health centers should give them the motivation to quit smoking, too.…”
Section: Discussionmentioning
confidence: 54%
“…The main substances that can be transferred to the nursing infant through maternal milk are: nicotine, benzene, formaldehyde, cyanide, carbon monoxide, carbon dioxide, dichlorodipehnyltrichloroethane, hydrogen, ammonia, aluminium, arsenic, and lead [32]. In addition to having adverse effects on the child, smoking can also alter the composition of maternal milk and reduce the production of prolactin and milk, leading to early weaning [33].…”
Section: Breast Feeding and Passive Smokementioning
confidence: 99%
“…Among the many effects that smoking can have on the child, some should be highlighted: oxidant damage from free radicals generated through smoke [19]; blocks lymphocyte proliferation and differentiation including suppression of antibody formation [33]; may promote inflammation through oxidative stress; distorts adaptative T-cell-mediated immunity, impair responses to pathogens, and suppres anti0tumor immune cell function [34] may alter lung and brain development in children; reduces mucociliary activity [35], alters the vascular permeability of the respiratory epithelium, causes hyperplasia of mucosal glands and increases mucus production; impaired lung function and increased respiratory symptoms [36]; compromises endothelial function, arterial elasticity and arterial intima-media thickness [37]- [39]; increases the risk of overweight and obesity [40]; increases the risk of dyslipidemia [41]; increases arterial pressure [42]; atherosclerosis [43]; risk of development of asthma and worsening of pre-existing asthma [44]; could express significant direct genotoxic effects in human cells [22]; increases sensitization to allergens and levels of total IgE; sudden infant death syndrome; changes in sleep and wake patterns [32]; pyloric stenosis, obesity, neurosensory hearing loss; increased risk of iodine deficiency and thyroid stimulating hormone [33]. In addition to these, other possible effects of passive smoking have been recently documented [45], such as adversely affects cognitive ability, language skill, and fine-motor function [46]- [49], diabetes mellitus type 2 [50], chronic pain in the head, back, joints and abdominal cavity [51], multiple sclerosis [52] and changes in the oral flora [53], increased risk of hospitalization for respiratory syncytial virus lower respiratory tract infection [54].…”
Section: Effects On Childrenmentioning
confidence: 99%
“…The authorities continue to support smoking cessation and reduction. Nicotine and its main metabolite cotinine can cause sleep disturbances, can increase the risk of iodine and thyroid stimulating hormone (TSH) deficiency, can reduce the count of pancreatic β cells and thus can increase the glucose level, can cause hyperleptinemia and neonatal nicotine withdrawal syndrome [6,7]. Nicotine and cotinine disappear from the milk by 3 h and 72 h respectively [7,8].…”
Section: Introductionmentioning
confidence: 99%